Evaluation of employee assistance programme in the Department of Public Works: Vhembe District - Khorombi, Ndivhuwo Nelly (My University, 2007)
An evaluation of Employee Assistance Programme is pivotal in any department or enterprise. An EAP must be evaluated to justify its existence to external authorities, to ascertain the extent to which the programme is fulfilling its objectives and to find ways to improve its performance. The purpose of this study was to evaluate the EAP within the Department of Public Works in Vhembe District specifically focusing on the employees’ awareness of the programme, its utilization, as well as programme adequacy. A quantitative approach was used in this study. Eighty six (86) employees from various levels in the Department were selected to participate in the study using a systemic random sampling in which every tenth person from the sampling frame was selected. Summary of the main findings The following is a summary of major findings from the study: 􀂃 The majority of the employees were aware of EAP within the Department of Public Works through meetings. 􀂃 The Employee Assistance Programme within the Department of Public Works was viewed as accessible by the majority of employees. 􀂃 The utilization rate of EAP within the Department of Public Works in Vhembe District was low, since only 29% of employees indicated that they had utilized the services before. 􀂃 The employees who had utilized the EAP were mainly referred by their supervisors while some referred themselves. Only ten percent (10%) of supervisors/managers indicated that they had referred employees to the EAP. The referral rate of employees to the EAP by supervisors/managers was low. 􀂃 EAP was viewed as confidential by the majority of employees within the Department and the level of employees’ trust to the EAP staff was high. v 􀂃 The majority of employees were not aware of the EAP policy and they had never participated in policy formulation. 􀂃 Most employees within the Department indicated that the EAP was addressing their personal problems, and the programme was viewed as useful (programme adequacy). 􀂃 The majority of employees were satisfied with the EAP within the Department of Public Works in Vhembe. 􀂃 Most employees identified a need for EAP staff to inform all employees within the Department about its services and to visit the Cost Centres frequently.
Thesis (M.A.) (Social Work) --University of Limpopo, 2007.
Keywords: Employee Assistance Programme; Employees; Awareness; Utilization; Penetration rate; Programme adequacy; Evaluation